New substituted quinoxalines inhibit triple-negative breast cancer by specifically downregulating the c-MYC transcription - Hu, Ming-Hao (Nucleic Acids Res, 2019)
Conventional chemotherapy remains the primary treatment option for triple-negative breast cancer (TNBC). However, the current chemotherapeutic drugs have limited effects on TNBC, and often lead to serious side effects as well as drug resistance. Thus, more effective therapeutic options are sorely needed. As c-MYC oncogene is highly expressed during TNBC pathogenesis, inhibiting c-MYC expression would be an alternative anti-TNBC strategy. In this study, we designed and synthesized a serial of quinoxaline analogs that target c-MYC promoter G-quadruplex (G4), which is believed to be a repressor of c-MYC transcription. Among them, a difluoro-substituted quinoxaline QN-1 was identified as the most promising G4-stabilizing ligand with high selectivity to c-MYC G4 over other G4s, which is distinguished from many other reported ligands. Intracellular studies indicated that QN-1 induced cell cycle arrest and apoptosis, repressed metastasis and inhibited TNBC cell growth, primarily due to the downregulation of c-MYC transcription by a G4-dependent mechanism. Notably, inhibition by QN-1 was significantly greater for c-MYC than other G4-driven genes. Cancer cells with c-MYC overexpression were more sensitive to QN-1, relative to normal cells. Furthermore, QN-1 effectively suppressed tumor growth in a TNBC mouse model. Accordingly, this work provides an alternative strategy for treating TNBC.